1998
DOI: 10.1021/om9802010
|View full text |Cite
|
Sign up to set email alerts
|

New Chiral N,S-Ligands Based on Oxazoline−Thioglucose Donors. Palladium(II)-Catalyzed Enantioselective Allylic Alkylation

Abstract: New bidentate ligands containing both chiral oxazoline and thiosugar elements, and also their 1,3-diphenylallyl Pd(II) complexes, have been prepared. The sugar is based on a 2,3,4,6-tetra-O-acetyl-β-d-glucopyranose moiety. These N,S-oxazoline−thioglucose ligands afford excellent ee's (90.2−96.9%) in the model enantioselective allylic alkylation reaction involving a 1,3-diphenylallyl precursor. 1H and 13C NMR spectra for the Pd compounds show that they exist in solution as a mixture of (syn/syn) exo and endo di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 21 publications
3
42
0
Order By: Relevance
“…For the latter ligand, using the centroids of the C12-C13 and C16-C17 double bonds, X1a and X1b, respectively, a twist of 4.8 o of the dihedral planes S1-Ir1-S2 and X1a-Ir1-X1b is found. A similar situation was observed for the Ir complex [Ir(cod){C[P(S)(Ph) 2 ] 3 }], [38] which showed a twist of 9 , respectively).…”
Section: Crystal Structure Of [Ir(cod)(5b)]bf 4 (10b)supporting
confidence: 72%
See 1 more Smart Citation
“…For the latter ligand, using the centroids of the C12-C13 and C16-C17 double bonds, X1a and X1b, respectively, a twist of 4.8 o of the dihedral planes S1-Ir1-S2 and X1a-Ir1-X1b is found. A similar situation was observed for the Ir complex [Ir(cod){C[P(S)(Ph) 2 ] 3 }], [38] which showed a twist of 9 , respectively).…”
Section: Crystal Structure Of [Ir(cod)(5b)]bf 4 (10b)supporting
confidence: 72%
“…[1,2] In particular, complexes containing thioether mixed-donor ligands such as the P,S-, [3][4][5][6][7][8] N,S- [9][10][11][12][13][14][15][16][17] and O,S- [18][19][20][21][22] donors have been successfully applied in asymmetric hydrogenation, [5,6,23] allylic substitutions [7][8][9][10]18] and enantioselective hydrosilylation of ketones. [4,23] In contrast, catalysts with chiral bidentate thioether ligands have been scarcely investigated, [24][25][26][27][28][29][30][31][32] although some have shown promising catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…2;3 However, only a few reports on the synthesis and application of ligands with type II, which have one of the substituent at the benzylic position, have appeared although the structure of type II ligands seems simple. 4 During the course of design, synthesis and application of chiral ligands in asymmetric catalysis, 5 we found that ligands 2 and 3, which have a substituent at the benzylic position, show higher catalytic activity. 6 Based upon these findings, other ligands with a substituent at the benzylic position have been synthesized and used in asymmetric catalysis to confirm if this phenomenon is general.…”
mentioning
confidence: 99%
“…This low enantioselectivity might be explained by the lower rigidity of the oxazolidine ring compared to the oxazoline ring. Other explanations are possible, such as the ability to form additional chiral centers at the nitrogen and sulfur atoms when complexed to the palladium center, [17,24] and the higher flexibility of the benzyl substituent on the oxazolidine unit compared to the phenyl substituent on the oxazoline ligands that have been studied (Figure 2, complexes 15 vs. 16). …”
Section: Resultsmentioning
confidence: 99%
“…(2) The steric effect: the final stereoselectivity is determined by the chiral moiety of the ligand favoring one of the two π-allyl conformations. Various chiral bidentate ligands with two different heterodonor atoms and different donorϪacceptor strengths, like (phosphanyl)oxazolines, [9] (phosphanyl)imines, [10] (phosphanyl)amines, [11] phosphite-oxazolines, [12] phosphaferrocene-oxazolines, [13] phosphane-phosphites, [14] (thio)oxazolines, [15] (thio)pyridines, [16] thioglucose-oxazolines, [17] phosphanyl sulfoxides, [18] and phosphito-thioethers, [19] form effective catalysts with palladium to induce high enantioselectivities. To our surprise, heterobidentate sulfur-nitrogen ligands have received little attention in the search for an effective catalyst.…”
Section: Introductionmentioning
confidence: 99%